2009
DOI: 10.1016/j.apcata.2009.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Pd/Ga2O3 methanol steam reforming catalysts: Part II. Catalytic selectivity

Abstract: Structure, morphology and composition of two Pd/Ga2O3 methanol steam reforming catalysts were correlated with the associated activity and selectivity changes in the methanol steam reforming reaction and linked to studies on pure Ga2O3 supports. For both systems, that are, a Pd/Ga2O3 thin film model catalyst and a powder-supported Pd catalyst, we identified a temperature range in which the reduction with hydrogen yields a single Pd-Ga bimetallic on a reduced oxide support, which in turn suppresses methanol dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
97
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(108 citation statements)
references
References 19 publications
9
97
2
Order By: Relevance
“…They attributed the catalytic activity for methanol synthesis to the reaction of polydentate carbonates with dissociatively adsorbed hydrogen on the Ga 2 O 3 surface, while the addition of Pd only accelerates the reaction by spillover of hydrogen [32]. Penner et al [34] and Lorenz et al [35], however, did observe Pd-Ga alloying and improved selectivity in steam reforming in a study focusing on Pd/ Ga 2 O 3 thin-film model catalysts, but identified different intermetallic compounds than Iwasa's group.…”
Section: Introductionmentioning
confidence: 99%
“…They attributed the catalytic activity for methanol synthesis to the reaction of polydentate carbonates with dissociatively adsorbed hydrogen on the Ga 2 O 3 surface, while the addition of Pd only accelerates the reaction by spillover of hydrogen [32]. Penner et al [34] and Lorenz et al [35], however, did observe Pd-Ga alloying and improved selectivity in steam reforming in a study focusing on Pd/ Ga 2 O 3 thin-film model catalysts, but identified different intermetallic compounds than Iwasa's group.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy, which involves the preparation of the Pd-In particles by reduction in hydrogen, has proven its capabilities in studies on the corresponding Pd-Ga system [7,8]. On the one hand the thin film model approach allows to prepare and characterize well-defined Pd-In bimetallic particles, grown on single-crystalline NaCl(001) surfaces, with respect to morphology, composition and catalytic selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The same applies to unsupported Pd-rich Pd 2 Ga samples 25 . In contrast, a supported Pd 2 Ga intermetallic compound on Ga 2 O 3 catalyst is highly active and selective as has been shown by Lorenz et al 22,26 . By comparison of the PdGa near surface intermetallic phase with Ga 2 O 3 -supported PdGa compounds, as e.g.…”
Section: Application Of the Uhv-setup And High Pressure Reaction Cellmentioning
confidence: 88%
“…By comparison of the PdGa near surface intermetallic phase with Ga 2 O 3 -supported PdGa compounds, as e.g. studied by Lorenz et al 22 , the importance of the (bi-)metal-oxide contact area could be directly demonstrated. temperature range of 543 K -573 K, the CO 2 -selective MSR reaction is prevalent, but above 573 K, the selectivity changes towards CO because the catalyst undergoes structural changes.…”
Section: Application Of the Uhv-setup And High Pressure Reaction Cellmentioning
confidence: 97%
See 1 more Smart Citation